RANCANG BANGUN WEBSITE DIGITAL LIBRARY MENGGUNAKAN TEXT TO SPEECH - Denisya Umam Hasbyalloh; Primadi Airlangga (KH. A. Wahab Hasbullah University, 2020)
The number of writings such as novels that are interesting and can be published for the public and has a selling point usually can only be read through school wall magazine makes the work less useful and less desirable. In this case on campus, UNWAHA has some wall magazine that contains many interesting writings such as novels, short stories, and others, but the works received less response and interest from students by providing a media or container that is easy and appropriate can be used as a solution to increase the interest of a writer and reader in publishing and enjoying a paper. And the media is Digital Library, a digital library application equipped with a Text to speech feature to attract readers. This research aims to design and build the digital library application on a website basis. The application is built with the Codeigniter framework while the database used is the MySQL. And from the User side of either Author or Reader, they can easily publish their work and they can also enjoy the work easily